Islamic Political Thought and Cultural Revival in Modern Indonesia - M. Din Syamsuddin (Studia Islamika, 1995)
Views of Islamic political thought, at least there are three currents of thought among Indonesian Muslim intellectuals; formalistic currents, currents substantivistik, and fundamentalist currents. One view of current formalistic, he said Islam is a universal religion and overall (total). He emphasized the power of God on earth and as the views of Islamic fundamentalism, the danger of "Westoxication" or "jahili modern society". For this group, Islam must be instituted in order to be a force for liberation in this world. This institutionalization will pave the way for the formation of modern society Qur'anis.DOI: 10.15408/sdi.v2i4.820